Analisis Implementasi Laporan Keuangan Berdasarkan Peraturan Menteri Koperasi No.14 Tahun 2015 Tentang Pedoman Akuntansi USPPS Oleh Koperasi (Studi Kasus Pada BMT Sumber Barokah Pulau Rakyat) - Lidiya Uzmasyah; Saparuddin Siregar; Atika Atika (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the application of financial reportsbased on Minister of Cooperatives Regulation No. 14 of 2015 concerning Guidelines USPPS Accounting By Cooperatives. The research method used in This research is a qualitative descriptive obtained from interviews and documentation. The research findings show that BMT Sumber Barokah Pulau Rakyat has not yet implemented financial reports based on the Regulations Minister of Cooperatives No. 14 of 2015 concerning USPPS Accounting Guidelines By Cooperatives in the presentation and preparation of financial statements. It can seen from the presentation and disclosure of transactions in the financial statements Balance Sheet Report on BMT Sumber Barokah and Temporary Syrirkah Funds combined with liabilities should be presented separately from liabilities.While in its financial accountability, BMT Sumber Barokah Pulau Rakyat only presents a statement of financial position (balance sheet), calculations equity, calculation of remaining results of operations (profit/loss), and statements of cash flows only. Matter is not in accordance with the Regulation of the Minister of Cooperatives No. 14 of 2015 About the USPPS Accounting Guidelines By Cooperatives which suggests there is reports on benevolent funds, reports on sources and use of zakat, as well as notes on financial statements Keywords: Financial Reports, Implementation of Financial Reports based on Minister of Cooperatives Regulation No. 14 of 2015 Concerning USPPS Accounting Guidelines By Cooperatives